2020
DOI: 10.1177/0885328220980278
|View full text |Cite
|
Sign up to set email alerts
|

Collagen membranes for skin wound repair: A systematic review

Abstract: Membranes or skin dressing are common treatments for skin wound injuries, collagen being one the most effective materials for their manufacturing. Many different sources of collagen with diverse methods of extraction and processing have been used, with evidence of positive effects on the stimulation of skin wound healing. In spite of these factors, there is still limited understanding of the interaction between collagen membranes and biological tissues, especially due to the series of different types of collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
(209 reference statements)
0
23
0
Order By: Relevance
“…The areas related to general physical fitness (crouching, kneeling down, walking at a brisk pace, playing a sport, exerting oneself physically) did not change significantly in any of the groups, which may be related to the age of the respondents, on average, 64 years. Studies evaluating other collagen products in the treatment of VLUs have also confirmed their benefits and showed improved quality of life [ 44 , 55 , 66 , 67 , 68 ]. Nevertheless, we are the first to apply collagen to the surrounding skin, showing an improvement in skin parameters.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The areas related to general physical fitness (crouching, kneeling down, walking at a brisk pace, playing a sport, exerting oneself physically) did not change significantly in any of the groups, which may be related to the age of the respondents, on average, 64 years. Studies evaluating other collagen products in the treatment of VLUs have also confirmed their benefits and showed improved quality of life [ 44 , 55 , 66 , 67 , 68 ]. Nevertheless, we are the first to apply collagen to the surrounding skin, showing an improvement in skin parameters.…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, collagen can be produced by heterologous expression in mammalian, insect, and yeast cells. It can also be produced by Escherichia coli [ 44 ]. Due to its low antigenicity and inherent biocompatibility with most endogenous tissue, natural collagen may be used for many pre- and post-operative surgical procedures (e.g., as adhesives), and also as a wound dressing.…”
Section: Discussionmentioning
confidence: 99%
“…While the wound closure rates in Cy-CBMG/laser group and Cy/laser group were nearly 100% and 87.4% in day 12, respectively, poor wound healing rates were observed in other groups (<75%). Collagen formation is a hallmark of wound regeneration and skin reconstruction [43]. As shown in Figure 6c, Masson's trichrome staining indicated that the regenerated skin tissues in Cy-CBMG/laser group displayed a shorter wound gap (Figure 6d) and denser collagen fiber deposition (Figure 6e), as compared with other groups.…”
Section: Wound Disinfection and Repair In Vivomentioning
confidence: 85%
“…A previous study Adverse events: (A) the pooled result; (B) sensitivity analysis. (6) demonstrated that collagen has a positive effect on wound healing by reviewing 16 studies (14 studies for animals and only 2 studies for humans). However, a metaanalysis was not performed due to high heterogeneity and patients with diabetes mellitus were excluded whereas we performed a meta-analysis and included diabetes mellitus patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a potential treatment, collagen dressings are applied in many fields such as chronic wounds, and reconstructive, separately or together with other materials ( 5 ). Meanwhile, Tiago et al also demonstrated that collagen was the most efficient treatment for skin wounds ( 6 ). Therefore, collagen is in a dominant position in wound healing.…”
Section: Introductionmentioning
confidence: 99%